Comparative analysis of MPPT techniques for PV applications - De Brito, Moacyr A. G.; Sampaio, Leonardo P.; Luigi, G.; E Melo, Guilherme A.; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a careful evaluation among the most usual MPPT techniques, doing meaningful comparisons with respect to the amount of energy extracted from the photovoltaic (PV) panel, PV voltage ripple, dynamic response and use of sensors, considering that the models are first implemented via MatLab/Simulink®, and after a digitally controlled boost DC-DC converter was implemented and connected to an Agilent Solar Array simulator in order to verify the simulation results. The prototype was built, the algorithms are digitally developed and the main experimental results are also presented, including dynamic responses and the experimental tracking factor (TF) for the analyzed MPPT techniques. © 2011 IEEE.
Keywords: Digital Control; MPPT Techniques; PV Applications; Tracking Factor for MPP; Agilent; Boost DC-DC converter; Comparative analysis; Digital control; MATLAB /simulink; Photovoltaic panels; Simulation result; Solar array simulators; Voltage ripples; DC power transmission; DC-DC converters; Digital control systems; Dynamic response; Renewable energy resources